Penerapan Terapi Doa untuk Menurunkan Kecemasan Pasien Pre-Operasi dengan General Anestesi di RSUD Dr. R. Goeteng Taroendibrata - Zafhira Araza; Tophan Heri Wibowo; Madyo Maryoto (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Surgical procedures performed under general anesthesia commonly cause preoperative anxiety in patients. Uncontrolled anxiety may interfere with patient readiness, affect physiological stability, and potentially delay surgery. Therefore, a complementary non-pharmacological intervention is needed, one of which is spiritual therapy through prayer. Objective: The purpose of this service was to provide spiritual comfort and reduce preoperative anxiety in patients undergoing general anesthesia through the implementation of prayer therapy. Method: This public service was conducted by implementing guided prayer therapy consisting of istighfar, remembrance (dzikir), and a tawakal prayer for approximately 5–10 minutes before surgery. The activity was carried out at RSUD dr. R. Goeteng Taroenadibrata Purbalingga involving 30 Muslim patients scheduled for surgery under general anesthesia. Anxiety levels were measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) before and after the intervention. Result: Prior to the intervention, most patients experienced moderate anxiety (56.7%) and severe anxiety (40.0%). After prayer therapy, anxiety levels decreased with the majority categorized as mild anxiety (80.0%), some moderate anxiety (16.7%), and a small proportion without anxiety (3.3%). Patients also appeared calmer, more cooperative, and mentally better prepared to undergo surgery. Conclusion: Prayer therapy is effective as a non-pharmacological intervention to reduce preoperative anxiety in patients receiving general anesthesia and has the potential to be implemented as a complementary spiritual care approach in perioperative services.